IMPROVEMENT OF READING COMPREHENSION OF GRADE 10 STUDENTS AT SMA DEZ DE DEZEMBRO, COMORO, DILI, TIMOR-LESTE THROUGH THE USE OF GRAPHIC ORGANIZERS - dosreis, ana joana; Tans, Feliks; Haan, Johnson Welem (Postgraduate School, Universitas Nusa Cendana, 2024)
This study aims to improve the reading comprehension of grade 10 students at Dez de Dezembro High School, Comoro, Dili, Timor-Leste, through the application of graphic organizers. Carried out during the 2024 academic year, this study involved a sample of 30 students. Data collection methods include observation checklists used during classroom action research, as well as preliminary and final tests. The findings from this two-cycle study show that the use of graphic organizers significantly improves students' reading comprehension. When integrated with skimming and scanning strategies, as well as communicative reading activities, this approach substantially enriches the teaching and learning process. Reading activities become more interactive and engaging, facilitating students' understanding of concise information and connections between ideas. As a result, students show noticeable improvement, with focus and active participation in the lesson. In addition, they become proficient in implementing various reading strategies, resulting in more effective and efficient reading comprehension.